2009
DOI: 10.1016/j.neuroimage.2008.11.011
|View full text |Cite
|
Sign up to set email alerts
|

A Tc-99m SPECT study of regional cerebral blood flow in patients with transient global amnesia

Abstract: Objectives This study aimed to determine whether regional cerebral blood flow (rCBF) is abnormal in patients who have Transient Global Amnesia (TGA). Methods We obtained noninvasive rCBF measurements using Tc-99m-ethyl cysteinate diamer Single Photon Emission Computed Tomography (SPECT) in 7 patients diagnosed with TGA within 4 days of onset of the amnestic episode while the patients were still symptomatic and in 17 age-matched healthy control subjects. We assessed memory functioning using the Hopkins's Verb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
4
14
0
Order By: Relevance
“…These findings are compatible with our previous study using VBM, which also found volume reductions in the left hippocampus only. This left lateralization is consistent with other previous studies using EEG and SPECT (Chung et al., ; Jang et al., ; Kwon et al., ). Kim et al.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are compatible with our previous study using VBM, which also found volume reductions in the left hippocampus only. This left lateralization is consistent with other previous studies using EEG and SPECT (Chung et al., ; Jang et al., ; Kwon et al., ). Kim et al.…”
Section: Discussionsupporting
confidence: 93%
“…Yang suggested that lateralized abnormalities in brain functioning may be an important component of the pathophysiology of TGA, as evidenced by a significantly decreased regional cerebral blood flow on the SPECT scans in the superior temporal, precentral, and postcentral gyri with a relative left dominance. 26 Mark reported that patients with left hippocampal sclerosis differ from normal subjects in the distribution of memory-encoding activity between left and right hippocampus. 27 The lateralization of MRI and SPECT in the patients was not significant, unlike that of the EEG ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…However, most studies have also noted concomitant decreased or increased changes in cerebral blood flow in other anatomical structures, such as unilateral or bilateral thalamic, prefrontal, frontal, amygdaline, striatal, cerebellar, occipital, precentral and post central areas (Eustache et al, 2000;Nardone et al, 2004). In some studies, no mesiotemporal changes, no cerebral changes, or a global hypo perfusion were detected (Chung et al, 2009). In summary, the imaging data derived from PET and SPECT studies are difficult to compare and interpret.…”
Section: Front Temporal Lobar Degenerationmentioning
confidence: 99%